The role of employee commitment on organizational performance and the intention to stay - Sencherey, Richmond Baffour; Kamil, Naail Mohammed; Zakari, Mariama; Xemalordzo, Enya Ameza (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study attempted to examine critically the influence of employee commitment on organizational performance and intention to stay at Kumasi Metropolitan Assembly (KMA), Kumasi – Ghana. A quantitative research methodology was employed in this study where two hundred and eleven (211) respondents were selected for the study using random sampling. The population consists of civil servants and other categories of work at Kumasi Metropolitan Assembly in Ghana. The questionnaires were distributed to respondents for data collection. Data were analyzed using SPSS. The study found that affective commitment and normative commitment significantly influence organizational performance. The study further found that affective commitment and normative commitment and continuance commitment significantly employees’ intention to stay. In practice, the management of KMA needs to take effective initiatives to increase employee commitment to the organization. Management can provide employees with training, and career development programs and increase their compensational packages. This will influence employees to remain loyal to the organization. This will also reduce employee turnover and intentions to stay in the organization. Also, the study recommends that the Management of KMA and other institutions alike should create value for the work activities and duties carried out by each employee in the organization. Creating value by recognizing individual efforts and rewarding positive behaviors will cause the employees to remain members of the organization because of the perception that they cannot secure better job opportunities elsewhere.